Yahweh and the origin of Yahwism : a critical evaluation - Mondriaan, Marlene E. (Old Testament essays, 2004)
The origin of Yahweh and Yahwism has been extensively debated the past few decades. From these debates, the Kenite hypothesis and the hypothesis to equate Yahweh in origin with the Canaanite El figure have emerged. These two hypotheses are tested and evaluated on the basis of a selection of Biblical texts. Deficiencies and contradictions in the arguments are pointed out. The epithet Yahweh is, inter alia, arbitrarily read into some texts. Furthermore, inferences that Yahweh essentially possesses El attributes are contradicted by references in the Masoretic Text whereby Yahweh is depicted as a storm god. It is concluded that there is a significant similarity between the portrayal of Yahweh and the traditional representation of the Ancient Near Eastern storm gods.